Children’s and adolescents’ internet use: Risks and opportunities - Grigutytė, Neringa; Raižienė, Saulė; Pakalniškienė, Vilmantė (Psichologija, 2021)
This paper presents the concept of risks and opportunities of children’s and adolescents’ Internet use. The research is a part of the project “Children’s and adolescents’ Internet use in Lithuania: possibilities and risks tendencies in EU context”, which was funded by a grant (No. S-MIP-17-1/LSS-250000-1087) from the Research Council of Lithuania. The main results are presented in comparison with Lithuanian and European studies. Conclusions and recommendations on how to ensure safe children’s Internet use on their own and to avoid potential risks, as well as how to open up the opportunities offered by the Internet are provided.